Studies on genetic variability, correlation and path co-efficient analysis in kachri (Indian Journal of Arid Horticulture, 2025)
The genetic variability, heritability in broad sense, genetic gain, correlation and path coefficient analysis were studied in 29 diverse populations of kachri. Wide range of variation was observed in most of the characters. The magnitude of PCV was greater than the corresponding GCV for all the characters indicating importance of environment in expression of characters. High values of PCV as well as GCV were recorded for yield per vine, weight of fruit and number of fruits per vine. Out of 14 characters studied, yield per vine and weight of fruit showed high GCV and heritability coupled with high genetic advance which showed that these two characters had additive gene effect and, therefore, they are more reliable for effective selection. Correlation coefficient revealed that fruit yield per vine can be successfully improved by making selection for higher fruit weight, more fruit length, greater fruit diameter and minimum node number at which first female flower appeared. Path coefficient analysis revealed that maximum weightage should be given primarily to number of fruits per vine, weight of fruit, diameter of fruit and node number at which first female flower appeared, while formulating selection indices for improvement of yield per vine in kachri.
Keywords: Genetic variability; correlation; path coefficient; kachri; Cucumis callosus